2016
DOI: 10.1021/acs.energyfuels.5b01328
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Asphaltenes’ Structural Phase Characteristics in the Process of Conversion of Heavy Oil in the Hydrothermal Catalytic System

Abstract: The composition of heavy crude oil from the Ashal’cha field (Volga-Ural Basin, Republic of Tatarstan) and the peculiarities of the changes of its asphaltenes’ structural phase characteristics in the model hydrothermal–catalytic system have been studied very thoroughly. It has been established that in the water vapor media the process of destruction of the heavy crude oil high-molecular-weight components with the new light fraction formation in the presence of a natural catalyst, namely, hematite, containing ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 37 publications
1
36
0
Order By: Relevance
“…However, many issues still remain unresolved. Works on finding optimal technologies aimed at increasing the efficiency of developing deposits of heavy oils and natural bitumens using thermal methods are carried out in many research centers and oil-producing companies [15][16][17][18][19][20][21][22][23][24][25][26][27]. Difficulties arising from the development of heavy oil fields are associated with two problems: first, unfavorable reservoir properties-low thermal conductivity, low permeability, and lack of reservoir energy; second, the hydrocarbon component of the bituminous reservoirs is in an inactive state [4,7,10,12,13,15,19].…”
Section: Introductionmentioning
confidence: 99%
“…However, many issues still remain unresolved. Works on finding optimal technologies aimed at increasing the efficiency of developing deposits of heavy oils and natural bitumens using thermal methods are carried out in many research centers and oil-producing companies [15][16][17][18][19][20][21][22][23][24][25][26][27]. Difficulties arising from the development of heavy oil fields are associated with two problems: first, unfavorable reservoir properties-low thermal conductivity, low permeability, and lack of reservoir energy; second, the hydrocarbon component of the bituminous reservoirs is in an inactive state [4,7,10,12,13,15,19].…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have found that steam flooding of heavy oil and oil-saturated rocks results in the destruction of the weakest carbon-heteroatom bonds with detachment of peripheral fragments from resins and asphaltenes and formation of lighter hydrocarbons [1][2][3][4][5][6][7][8][9][10][11]. The destruction of asphaltenes under the steam treatment occurs primarily through the weak aliphatic sulfide bonds ( Figure 1) that are destabilized by electron-withdrawing functional groups.…”
Section: Catalytic Aquathermolysismentioning
confidence: 99%
“…Such a process initiates already at 120 • C [13]. The destruction products of resins and asphaltenes joins other fractions, which determines reduction in heavy oil viscosity and increase in heavy oil recovery [3,4,7]. The schematics of the main chemical reactions that describe the catalytic aquathermolysis process are illustrated in Figure 1.…”
Section: Catalytic Aquathermolysismentioning
confidence: 99%
See 1 more Smart Citation
“…Innovative technologies for the development of hard-to-recover hydrocarbon resources represents a highly relevant topic nowadays [27][28][29]. Alternative hydrocarbon resources, such as carbonate deposits containing organic matter, are widespread in Russia, China, Jordan, Brazil, Morocco, Australia, Estonia, USA, Canada, Zaire, Italy, France, etc.…”
Section: Introductionmentioning
confidence: 99%